A Preliminary Investigation of CSPN in the HASH Database - Quentin A. Parker; Zou Xiang; Andreas Ritter (Galaxies, 2022)
We present some preliminary findings on the population of planetary nebula where central stars (CSPN) have been independently identified in the HASH catalogue. Many new discoveries and candidates have been found (416 at the time of this writing), adding significantly to the previously known sample of about 600. We also present results from a comparison between our own HASH measurements of CSPN and those provided in existing CSPN catalogues and those from Gaia. We show the value of a federated, multi-wavelength database of Galactic PNe like HASH in terms of not only uncovering faint, new CSPN but of assisting in correct identifications, removing PN mimics with apparent CSPN, correcting incorrect assignments and providing improved positions. HASH provides the community with a comprehensive and reliable resource for any study of the CSPN population of Galactic PNe.